Examen especial a servilubricar s.a. de la ciudad de Machala, a cuentas y documentos por pagar, y, otras cuentas por pagar, durante el periodo 2020. - Godoy Calva, Ginger Betzabeth (2022)
The Curricular Integration work called “SPECIAL EXAM TO SERVILUBRICAR S.A OF THE CITY OF MACHALA TO ACCOUNTS AND DOCUMENTS PAYABLE, AND OTHER ACCOUNTS PAYABLE, DURING THE 2020 PERIOD” was aimed at reaching the set objectives which refer to evaluating the system internal control according to the provisions, laws, regulations and regulations in force for Servilubricar S. A.; determine the reasonableness of the information reflected in the Financial Statements of Accounts and Documents Payable, and, Other Accounts Payable and prepare the report of the special exam that contains comments, conclusions and recommendations that serve as a guide to the directors of Servilubricar S.A, to take appropriate corrective actions. In the execution of the Special Exam, Servilubricar S.A was visited to collect timely information that allows a clearer vision of the company; then, internal control evaluations were carried out on each of the items to determine the reasonableness of the balances of the Items Accounts and Documents Payable and Other Accounts Payable presented in the financial statements, which were reviewed, analyzed and verified, verifying compliance with current regulations and Generally Accepted Accounting Principles. By carrying out the procedures according to the programs, work papers were designed, based on the international auditing principles and standards focused on verifying and analyzing the activities and operations carried out by Servilubricar S.A. to determine the shortcomings or mistakes to make corrective and pertinent decisions by the provisions, laws, principles and regulations in force.